Characteristics of Parents With High Expressed Emotion and Related Factors: A Study of Parents of Adults With Schizophrenia. Issue 12 (December 2018) - Kageyama, Masako; Solomon, Phyllis
Abstract : Abstract: This study aimed to clarify characteristics of parents with high expressed emotion (EE) and related factors among parents of adults with schizophrenia. In total, 73 (25.3%) of the 289 parents had high EE (Family Attitude Scale [FAS] score ≥60), and 216 (74.7%) had low EE (FAS score <60). A multiple logistic regression analysis showed that high EE parents were more distressed (odds ratio [OR] = 1.27; 95% confidence interval [CI] = 1.16–1.39) and experienced more physical violence from their adult children with schizophrenia (OR = 2.86; 95% CI = 1.28–6.43); the children with schizophrenia had been hospitalized at time of survey (OR = 6.54; 95% CI = 1.10–38.89) and were less likely to attend rehabilitation services (OR = 2.56; 95% CI = 1.06–6.17). Practitioners need to provide crisis intervention, home-visiting services, and support services for parents during hospitalization of their children with schizophrenia.